Urothelial Bladder Cancer with Cavitary Lung Metastases - Anil Kurian; Jason Lee; Abraham Born (Canadian Respiratory Journal)
Transitional cell carcinoma (TCC) of the bladder tends to remain superficial; however, in 5% to 20% of cases, it progresses to muscle invasion and, more rarely, can metastasize. TCC of the bladder primarily spreads via regional lymphatics. The most common sites of distant metastases of TCC are the liver, lung, mediastinum and bone. Long-term survival of patients with metastatic bladder cancer is rare. Patterns of pulmonary metastasis include multiple nodules, a solitary mass or interstitial micronodule. When multiple nodules are present, they are round and well-circumscribed, without calcification or cavitation. An unusual case of rapidly metastatic TCC to the lung causing large cavitary masses and nodules is presented. Imaging performed after the patient began chemotherapy revealed widespread necrosis of the metastatic cavitary masses causing moderate volume hemoptysis.